Peran Komunikasi Pemerintahan dalam Penanganan Lingkungan Kumuh - Indriyati Kamil (MediaTor)
Linggar Urban Village is one of the villages in Rancaekek sub-district of Bandung Regency with a fairly high slum category and lack of infrastructure facilities. One of the causes of the slums in Linggar village is the contaminated river and paddy fields by garbage and factory waste. Therefore, appropriate operational strategies are needed to address the environmental issues. The result of the research shows that communication of Linggar village government is done by using synergy of collaboration platform, linggar village government using principles of openness and transparency in coordination and communication network with stakeholders such asthe government of central, provincial, district-city, business, and society. Linggar local government seeks to encourage the industrial sector to carry out environmental responsibility by reducing the impact of pollution due to industrial waste and continuously providing environmental protection in residential areas and community land. The communication is also done by the local government of linggar village by facilitating the planning of environmental infrastructure, also the settlement by using the concept of community action plan (CAP), strengthening the community institution by forming community association of Pawapeling, making citizen media and directed focus group discussion